Deciphering a proliferation-essential gene signature based on CRISPR-Cas9 screening to predict prognosis and characterize the immune microenvironment in HNSCC - Ke-ling Pang; Pian Li; Xiang-Rong Yao; Wen-Tao Xiao; Xing Ren; Jun-Yan He (BMC Cancer)
Abstract Background Head and neck squamous cell carcinoma (HNSCC) is a highly aggressive malignancy with a poor prognosis. Identifying reliable prognostic biomarkers and therapeutic targets is crucial for improving patient outcomes. This study aimed to systematically identify proliferation-essential genes (PEGs) associated with HNSCC prognosis using CRISPR-Cas9 screening data. Methods CRISPR-Cas9 screening data from the DepMap database were used to identify PEGs in HNSCC cells. A prognostic PEGs signature was constructed using univariate Cox regression, least absolute shrinkage and selection operator (LASSO) Cox regression, and multivariate Cox regression analyses. The predictive accuracy of the signature was validated in internal and external datasets. Weighted gene co-expression network analysis (WGCNA), gene set enrichment analysis (GSEA), and immune infiltration analysis were used to investigate the underlying mechanism between high and low-risk patients. Random forest analysis and functional experiments were conducted to investigate the role of key proliferation essential genes in HNSCC progression. Results A total of 1511 PEGs were identified. A seven-gene prognostic PEGs signature (MRPL33, NAT10, PSMC1, PSMD11, RPN2, TAF7, and ZNF335) was developed and validated, demonstrating robust prognostic performance in stratifying HNSCC patients by survival risk. WGCNA and GSEA analyses revealed a marked downregulation of immune-related pathways in high-risk patients. Immune infiltration analysis validated those high-risk patients had reduced immune scores, stromal scores, and ESTIMATE scores, as well as decreased infiltration of multiple immune cell types. Among the identified genes, PSMC1 was highlighted as a pivotal regulator of HNSCC proliferation and migration, as confirmed by functional experiments. Conclusions This study identifies a novel PEGs signature that effectively predicts HNSCC prognosis and stratifies patients by survival risk. PSMC1 was identified as a key gene promoting malignant progression, offering potential as a therapeutic target for HNSCC.